Pencarian Lokasi Tempat Penyewaan Mobil Daerah Kota Pangkalpinang Berbasis Sistem Informasi Geografis - Delpiah Wahyuningsih; Wirriyawan Azzaki (Jurnal Nasional Teknologi dan Sistem Informasi, 2016)
Abstract – In general, the transport easier for people to help drive the take somewhere in the heading, with high mobility, a little time transport becomes an important part in supporting the speed and efficiency of work in the community, to support community facilities require that a rental car right place. But there are still many people who still do not know the location of car rental places scattered in the Region Pangkalpinang. The research objective is to provide facilities for the comfort of the car in Pangkalpinang tenants in finding information about the car rental place, making the application of geographic information system can provide information on the location of the car rental place using media websites, the study was conducted using a waterfall. This research results in the form of WebGIS, the location where a rental car will be displayed as detailed as possible in a web interface that allows the public.